Conciliation and Confession: The Struggle for Unity in the Age of Reform, 1415 - 1648 - Vidal, Jaime R. (Cistercian studies quarterly, 2005)
Reviews the book "Conciliation and Confession: The Struggle for Unity in the Age of Reform, 1415-1648," edited by Howard P. Louthan and Randall C. Zachman.